Facilitating art and design education students development of technological, pedagogical, skills and content knowledge through TPSACK courseware / Roslaili Anuar - Anuar, Roslaili (2020)
Art and Design Education is a focused area involving the nature of knowledge of technology, pedagogy and content, as well as the component of knowledge of artistic skills. The objective of this study is to design a courseware, namely TPSACK, a courseware for students of art and design education to develop their artistic skills and knowledge. Studying the TPACK framework has helped develop TPSACK courseware, which investigates the artistic skills required by the students of Art and Design Education as future teachers. The development of the TPSACK courseware explores complex roles and interplay during the learning phase between the four bodies. The interplay between these four bodies produces flexible knowledge to effectively integrate technological skills in the learning process. The quantitative method was used to conduct the survey analyzed through SPSS. Research results show a significant role in integrating technology with specific artistic skills to improve student motivation and knowledge. The mean score of TPSACK courseware is significant to enhance the artistic skills among them. In conclusion, the work presents a descriptive model of TPSACK courseware to improve the knowledge of artistic skills as well as the knowledge of technology, pedagogy and content. It also provides insight to guide the achievement and motivation of artistic skills among the Art and Design Education students.